Envolvimento da proteína neuronal sensora de cálcio-1 (NCS-1) na sinalização muscarínica em células PC12 - Melissa Monteiro Guimaraes (2007)
Neuronal calcium sensor-1 (NCS-1) belongs to the superfamily of EF-hand Ca2+ binding protein. Overexpression of NCS-1 was implicated on potentiation of synaptic transmission and plasticity in many experimental models. In this study we investigated the possible involvement of NCS-1 in the facilitation of glutamate release evoked by two distinct stimuli in the neuronal-like pheochromocytoma (PC12) cell: membrane depolarization induced by 60mM KCl and GPCR activation induced by 300ìM carbachol (CCH). Both KCl depolarization and G-protein coupled receptor activation by CCH evoked glutamate release from PC12 wild type cells (PC12-wt) and PC12 cells stable overexpressing NCS-1 (PC12-NCS-1) compared with control conditions. Both KCl depolarization and CCH stimulation were more efficient to evoke glutamate release from PC12-NCS-1 cells when compared with release evoked from PC12-wt cells. The increased glutamate release induced by CCH from PC12-NCS-1 cells was independent of extracellular calcium entry, however this effect was dependent on extracellular calcium influx when depolarized with KCl. At permeabilizing conditions both PC12-NCS-1 and PC12-wt stimulated with CCH were able to increase glutamate release compared with non-stimulated cells indicating that part of glutamate release could be originated from vesicles source. Thus, our results suggest together that the NCS-1 facilitation of glutamate release could respond to different stimuli and is related to the increase in intracellular calcium originated from the extracellular compartment when associated to depolarization stimuli and from intracellular stores when associated to GPCR activation.